PENDIDIKAN DAN PELATIHAN PEMBUATAN “MIKOPLUS” SEBAGAI TAMENG DAN PENEROBOS DI SISTEM PERAKARAN TANAMAN - Budiono (Najah: Journal of Research and Community Service, 2023)
This community engagement initiative revolves around providing education and training on the manufacture of "MIKOPLUS," a protective shield and penetration tool for plant root systems. The program aims to empower local farmers and gardeners with innovative techniques to improve plant health and growth. Through workshops and hands-on training, participants are equipped with the skills to make and use the MIKOPLUS device effectively. The program emphasized sustainable practices to nurture strong plant root systems, promoting increased resistance to external stresses. Initial results highlight an increase in crop vitality and yields among participating farmers. This initiative underscores the potential of knowledge dissemination and hands-on training in advancing sustainable agricultural practices and fostering community-driven innovation.